The 2000 presidential election - Landau, Elaine (New York Children's Press, 2002)
Explores the people and events surrounding the 2000 presidential election
American Corner
Includes bibliographical references (p. 46) and index
11
Keywords: Elections; Presidential candidates -- United States -- History -- 20th century -- Juvenile literature; Presidents -- Election -- 2000; Presidents -- United States -- Election -- 2000 -- Juvenile literature; United States -- Politics and government -- 1993-2001 -- Juvenile literature